Clean coder (Clean Coders video series) - Martin, Robert C. (Addison-Wesley Professional, 2017)
"Get ready for something very different. This ain't no screen cast. This ain't no talkin' head lecture. This is an Uncle Bob Video! This is like watching Uncle Bob on stage, but more so. This is high content education that will hold your attention and stimulate your thoughts with its impactful and energetic style. The Clean Coder Video Series contains Uncle Bob's Java Case Study series by Robert "Uncle Bob" Martin and Micah Martin from CleanCoders.com."--Resource description page.
Title and publication information from resource description page (Safari, viewed June 29, 2017)
Keywords: Computer programmers -- Professional ethics; Computer programming -- Moral and ethical aspects; Computer software -- Reliability; Software reengineering; Programmeurs; Déontologie; Programmation (Informatique); Aspect moral; Logiciels; Fiabilité; Logiciels; Remaniement; Computer programming; Moral and ethical aspects; Computer software; Reliability; Electronic videos